OPTIMALISASI HASIL BELAJAR MEMAINKAN MELODI TANGGA NADA PERUBAHAN MENGGUNAKAN ALAT MUSIK PIANIKA DENGAN TEKNIK JIGSAW (Harmonia: Journal of Arts Research and Education, 2009)
Then study was coducted clasroom action research study in which was 8th-gradestudents. The study was conducted in two cycles beginning with the pre-cycle andfollowed-up with the cycle II which each cycle through the for stages, namelyplanning, implementation of action, observation and reflection.Data collection techniques used were technical tests, observations, andinterviews. Techniques of data analysis using quantitative techniques toprocess data from the test results of students based on the number of values,while the techniques used to analyze qualitative data such as non-testquestionnaire, observation, and interviews. The results showed that an increasein each cycle, from pre-cycle of 38 students who attended by 37 studentsbecause of 1 student permit in sick, as many as 24 students or 64.85% completeand as many as 13 students or 35.15% have not completed. In cycle I of 38students there are 34 students or 89.47% have been completed and 4 studentsor 10.53% have not finished studying. In cycle II, an increase of more than 38students by 36 students or 94.74% and 2 or 5.26% of students have not studiedthoroughly. Based on the above results it is impotant that learning to cooperatewith jigsaw technique is one alternative that can be used to improve the qualityof teaching and student learning outcomes.Kata kunci: optimalisasi, hasil belajar, melodi, tangga nada perubahan, jigsaw